MODEL OPTIMALISASI DAYA UNGKIT KAMPUNG HIDANGAN EKONOMI KECIL (HEK) BEBAS TUBERKULOSIS DI KOTA SURAKARTA - Bhisma Murti; Diffah Hanim; Anik Lestari; Eti Poncorini Pamungkas (JURNAL LITBANG PROVINSI JAWA TENGAH, 2010)
Intervention model consisting of group education, counseling, and leaflet used for optimizing the promotion of Hidangan Ekonomi Kecil (HEK) kampongs as a strategy for the prevention and control of tuberculosis has not been implemented. Tuberculosis (TB) is a public health importance at the global, regional, national, and local level. In line with this background, a research question was raised, i.e. what is the appropriate model for optimzing the promotion of HEK kampongs for the prevention and control of tuberculosis and the improvement of social welfare. This study aimed to examine the intervention model for optimizing the promotion of HEK kampongs for the prevention and control of tuberculosis and the improvement of social welfare. This study was an action research. The intervention comprised group education, counseling, and use of leaflet. The independent variable was an intervention comprising group education, counseling, and use of leaflet. The dependent variables included health-related behavior, quality of environmental health, and ability to pay. Continuous data was described by mean and SD. Categorical data was described by percentage. The effectiveness of intervention was analyzed by McNemar nonparametric test. The results showed that HEK is an important employment in the informal sector, which provides income for the economically weak community. This enterprise is acceptable and is needed by the community. Buyers of HEK are usually community members with low or medium income. The mean profit is Rp 38,500 per day, ranging from Rp 25,000 to Rp 300,000 per day. Mean net income from HEK is Rp 1,021,774 per month, median Rp 900,000 per month, ranging from Rp 560,000 to Rp 2,600,000 per month. Living condition around HEK kampongs has yet to need health requirement. The health intervention can help change the behaviors of the sellers, family members, and buyers, to have healthy behaviors. This study concludes that the promotion of HEK kampongs for the prevention and control of tuberculosis, and the improvement of social welfare can be attained by an intervention that include group education, counseling, and use of leaflet.